UNICORN: a unified approach for localizing non‐deadlock concurrency bugs1. (9th March 2014) - Park, Sangmin; Vuduc, Richard; Harrold, Mary Jean; Farchi, Eitan; Hierons, Robert M.; Lourenço, João
Summary UNICORN is an automated dynamic pattern‐detection‐based technique that finds and ranks problematic memory access patterns for non‐deadlock concurrency bugs. It monitors pairs of memory accesses, combines the pairs into problematic patterns and ranks the patterns by their suspiciousness scores. It detects significant classes of bug types, including order violations and both single‐variable and multivariable atomicity violations, which have been shown to be the most important classes of non‐deadlock concurrency bugs. This paper describes the UNICORN approach, its implementations in Java and C++, and evaluates these implementations empirically. The evaluation shows that UNICORN can effectively compute and rank the patterns that represent concurrency bugs, and perform computation and ranking with reasonable efficiency. Copyright © 2014 John Wiley & Sons, Ltd.